O13.2. COMPARATIVE RISK OF PSYCHOSIS WITH AMPHETAMINE VERSUS METHYLPHENIDATE IN ADOLESCENTS AND YOUNG ADULTS WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER. (9th April 2019) - Moran, Lauren; Ongur, Dost; Hsu, John; Castro, Victor; Perlis, Roy; Schneeweiss, Sebastian
Abstract: Background: Prescription stimulant use (amphetamine and methylphenidate) for the treatment of attention deficit hyperactivity disorder (ADHD) is increasing. In 2007, the US Food and Drug Administration mandated changes to stimulant prescribing labels based on findings of new-onset psychosis in patients without pre-existing disease. Although these changes were mandated over 10 years ago, there has been no systematic study of the comparative risk of psychosis between amphetamine and methylphenidate. Studies of dopaminergic function in patients with psychotic disorders have demonstrated increased presynaptic dopaminergic capacity and greater amphetamine-induced release of dopamine compared to controls. In contrast, a meta-analysis has shown no differences in dopamine transporter availability between patients with schizophrenia and controls. The dopaminergic effects of amphetamine are more consistent with abnormalities observed in psychosis than methylphenidate. We sought to compare the risk of psychosis in adolescents and young adults with ADHD who are new users of amphetamine versus methylphenidate. Methods: This is a cohort study of patients 13 – 25 years old with an outpatient diagnosis of ADHD from two commercial insurance claims databases who started taking amphetamine or methylphenidate between January 1, 2004 and September 30, 2015. The outcome was a diagnosis of psychosis requiring treatment with an antipsychotic medication within 60 days. Two studies were conducted to validate this outcome definition with positive predictive values of 93.1% and 91.3%. We used 1:1 propensity score (PS) matching to match patients on a set of 50 covariates measuring ADHD severity, psychiatric comorbidity, psychotropic medication use, substance use and healthcare utilization. We estimated hazard ratios (HR) in PS-matched patients. Results from the two databases were pooled using fixed effects meta-analysis. Results: A total of 221, 846 participants in the propensity score matched subsets with 143, 286 person-years of follow-up experienced 343 psychotic events (2.4 per 1, 000 person-years). Use of amphetamine increased substantially over the study period with preferential prescribing of amphetamine to older patients. The majority of patients were prescribed stimulants by family/internal medicine physicians, who had the highest prescribing rates of amphetamine (72.5%) compared to pediatricians (51.6%) and psychiatrists (63.7%). Use of amphetamine was associated with an increased risk of psychosis with a combined HR of 1.65 (95% CI 1.31 to 2.09) based on 237 psychotic events in amphetamine users and 106 psychotic events in methylphenidate users. Findings from the primary analysis were supported by a range of sensitivity analyses using increasingly stringent definitions of psychosis and study design modifications. In addition, negative control analyses using various substance use disorders, including cannabis, as outcomes demonstrated no significant differences between the two exposure groups. Discussion: Amphetamine use is associated with an increased risk of treatment-emergent psychosis compared to methylphenidate among adolescents and young adults with ADHD.